EnCube : the art of concealment - Sua, James Kah Yong (2017)
EnCube is a piece of bespoke furniture that provides containment to our precious objects. With the secret compartments dedicated to each objects, not only it designate a specific space to them but they remains concealed from outsiders. Only with the user's knowledge, one would be granted access to the treasured pieces. Through rekindling, we could reminisce the memories and relationship of our sentimental items, while developing a form of sustainable practice.